2022
DOI: 10.1039/d2cp01754g
|View full text |Cite
|
Sign up to set email alerts
|

The destructive mechanism of Aβ1–42 protofibrils by norepinephrine revealed via molecular dynamics simulations

Abstract: Amyloid-β (Aβ) fibrillary plaques represent the main hallmarks of Alzheimer’s disease (AD), in addition to tau neurofibrillary tangles. Disrupting early-formed Aβ protofibril is considered as one of the primary therapeutic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Norepinephrine binds to the Aβ dimer in its hydrophobic (K16-A21) and C-terminal (I31-V36) regions predominantly and also disrupts the global conformation of the Aβ protofibrillar structure by interacting with the N-terminal residues of the protofibrils. The disruptive potential is higher for deprotonated norepinephrine compared to the protonated one . The β-strands formed between the L12-H18 and L27-G33 regions of hIAPP, which stabilize the peptide self-assembly, are also hampered when norepinephrine preferentially interacts with the C-terminal β-prone region .…”
Section: Anti-amyloid Activity Of Non-polyphenolic Catechol Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Norepinephrine binds to the Aβ dimer in its hydrophobic (K16-A21) and C-terminal (I31-V36) regions predominantly and also disrupts the global conformation of the Aβ protofibrillar structure by interacting with the N-terminal residues of the protofibrils. The disruptive potential is higher for deprotonated norepinephrine compared to the protonated one . The β-strands formed between the L12-H18 and L27-G33 regions of hIAPP, which stabilize the peptide self-assembly, are also hampered when norepinephrine preferentially interacts with the C-terminal β-prone region .…”
Section: Anti-amyloid Activity Of Non-polyphenolic Catechol Derivativesmentioning
confidence: 99%
“…The disruptive potential is higher for deprotonated norepinephrine compared to the protonated one. 78 The β-strands formed between the L12-H18 and L27-G33 regions of hIAPP, which stabilize the peptide self-assembly, are also hampered when norepinephrine preferentially interacts with the C-terminal β-prone region. 79 Similarly, norepinephrine destabilizes tau protofilaments by binding with the charged E338, E342, D348, D358, and E372 and aromatic Y310, P312, H374, and F378 residues through π−π stacking and hydrogen-bonding interactions.…”
Section: Anti-amyloid Activity Of Non-polyphenolic Catechol Derivativesmentioning
confidence: 99%
“…Furthermore, it provides the coordinates for the whole range of amino acids, i.e., 1–42, and so serves as one of the most relevant target structures for structure-based computational study. Certain studies included only pentamer units of protofibrils and so ignored the sites in the interfacial region. Here we include the entire protofibril, and so the molecular docking algorithm could locate binding sites on the surface, in the core, and in the interfacial region (see Figure ). As the binding site details for DANIR-2c are not available, we performed a blind docking by including the entire fibril within the grid box.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Razzokov and co-workers found that 3% of Met35 oxidation of an Aβ 11–42 pentamer led to a small destabilization in the structure of the pentamer and further increases of oxidation levels (9 and 15%) led to higher structural fluctuations and destabilization . MD simulation has also been used to study early steps of Aβ oligomer destabilization by the binding of a number of ligands. …”
Section: Introductionmentioning
confidence: 99%
“… 56 MD simulation has also been used to study early steps of Aβ oligomer destabilization by the binding of a number of ligands. 57 60 …”
Section: Introductionmentioning
confidence: 99%